Absolute beginner's guide to Wi-Fi wireless networking - Davis, Harold, 1953- (Que, 2004)
Absolute Beginner's Guide to Wi-Fi is a book for beginners who want to join the Wi-Fi revolution. Using easy-to-understand language, this book teaches you all you need to know about Wi-Fi, from choosing the Wi-Fi system that is right for you to adding a Wi-Fi card and related software to finding hotspots and access points. With the help of this book, you will be able to configure a home network and share internet connections quickly and easily. In addition, the book covers all important security issues so that a user is less exposed to threats, as well as the dos and don'ts of traveling with a Wi-Fi enabled laptop.